1999
DOI: 10.1200/jco.1999.17.5.1558
|View full text |Cite
|
Sign up to set email alerts
|

Small Noncleaved, Non-Burkitt's (Burkitt-Like) Lymphoma: Cytogenetics Predict Outcome and Reflect Clinical Presentation

Abstract: SNC-NB lymphoma is a clinically and cytogenetically heterogenous disease. Dual translocation of c-myc and bcl-2 is characterized by a rapid clinical course and extremely poor outcome. This latter entity may represent the most clinically aggressive lymphoma thus far characterized and warrants intensive investigational treatment where feasible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
116
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(124 citation statements)
references
References 27 publications
7
116
0
Order By: Relevance
“…The largest study published to date included 12 cases, six cases of t(14;18) with t(8;14), and six cases of t(14;18) with t(8;22). 12 These patients presented with advanced disease and had a poor prognosis, and six cases had a history of follicular lymphoma. Thangavelu et al 13 reported six cases with t(14;18) and 8q24 translocation: three that had t(8;14), and three that had t(8;22).…”
Section: Discussionmentioning
confidence: 99%
“…The largest study published to date included 12 cases, six cases of t(14;18) with t(8;14), and six cases of t(14;18) with t(8;22). 12 These patients presented with advanced disease and had a poor prognosis, and six cases had a history of follicular lymphoma. Thangavelu et al 13 reported six cases with t(14;18) and 8q24 translocation: three that had t(8;14), and three that had t(8;22).…”
Section: Discussionmentioning
confidence: 99%
“…28,29 The presence of an additional translocation as found in other types of B-NHL (for example, involving BCL2, BCL6 and/or CCND1) or a complex karyotype with multiple gains and/or losses would rather represent another type of B-NHL or a secondary transformed lymphoma. 30 This is supported by the publication of the MMML where array based comparative genomic hybridization (arrayCGH) was used to study genomic copy number imbalances in addition to fluorescent in situ hybridization (FISH) analysis for MYC, BCL2 and BCL6 translocations. In contrast to molecular BL, non-molecular BL were characterized by a less frequent IG-MYC translocation and by more additional genomic aberrations.…”
Section: Role Of Genetics In the Diagnosis Of Blmentioning
confidence: 96%
“…Various authors have already suggested that such DH BL cases should be considered a separate entity from 'true' BL. 30,54,55 When comparing the 44 BL IG-MYC DH cases with the core subset, they appeared to be two separate entities. DH BL patients were much older (mean 51 years, Po0.0001, Figure 2), very much similar to the other B-NHL group.…”
Section: Bl With a Non-ig-myc Translocation (Bl Non-ig-myc) Is A Rarementioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12][13][14] Numerous case series of MYC/BCL2 double-hit lymphoma are reported in the literature. [15][16][17][18][19][20][21][22][23][24] MYC/ BCL2 DHLs represent B10% of all lymphomas that otherwise resemble diffuse large B-cell lymphoma (DLBCL). 10 Although different studies have focused on different aspects or details of double-hit lymphoma, all studies suggest that patients with these lymphomas commonly have an aggressive clinical course characterized by advanced stage disease, extranodal involvement, and high serum lactate dehydrogenase levels.…”
mentioning
confidence: 99%
“…15,20,22,23 To our knowledge, however, little is known about atypical DHL and there is no large study in the literature that has focused on atypical MYC/BCL2 double-hit lymphoma. In this study, we assess the clinicopathologic, immunophenotypic, and cytogenetic features of a large group of patients with atypical double-hit lymphoma, and compare this patient group to a group of patients who had typical double-hit lymphoma as well as a group of patients who had DLBCL not associated with either MYC or t(14;18)(q32;q21)/ IGH@BCL2.…”
mentioning
confidence: 99%